PENERAPAN MODEL MULTIDEMENSIONAL SCALING (MDS) DALAM PEMBIAYAAN BANK SYARIAH DI PULAU SULAWESI DALAM MENDUKUNG SDGs - Trimulato Trimulato (JASIE, 2022)
The development of the Islamic banking industry continues to experience very good growth. This can be seen from the assets of Islamic banking which continues to increase and the public's interest in using Islamic banking products. One of the Islamic banking products is financing that is channeled to support the real sector. Sulawesi Island is one of the areas that have the potential to absorb Islamic banking financing. Every Islamic bank financing on the island of Sulawesi has a role in supporting the SDGs program through increased economic activity. The purpose of this study is to describe the development of financing in Islamic banks, as well as to describe the role of financing on the island of Sulawesi to support the SDGs. The method used in this research is qualitative. The data source used is secondary data, data that has been presented by institutions such as the Financial Services Authority (OJK). Data collection techniques through literature study. The analytical technique used in this research is Multidimensional Scaling (MDS). The results showed the development of Islamic banking financing in the period July 2020 to July 2021 the development of Musyarakah financing at BPRS grew by 43 percent, Murabahah grew 8.6 percent in BUS, and Qard grew in UUS. The analysis of the Multidimensional Scaling Model shows that the financing of BUS, UUS, and BPRS on the island of Sulawesi, South Sulawesi has a long-distance, for other areas it is close or similar. Financing distributed by Islamic banks in Sulawesi Island has a role in supporting the SDGs, at the point of reducing poverty, reducing hunger, encouraging economic growth, reducing inequality, and supporting sustainable production and consumption patterns.